Unripe Papaya (Carica papaya L.) Seed Hexane Fraction Extract Inhibits Male Mice (Mus musculus) Spermatogenesis Stronger Than Unripe Papaya Seed Methanolic Extract - Satriyasa, Bagus Komang (BALI MEDICAL JOURNAL, 2016)
Background: Men and women have the same rights and obligations in family planning program. Practically, participation in family planning program is still predominated by women while participation of men is still low. Low participation of men in family planning program is due to very limited choices in male contraceptive method. In recent years, studies have been refocused on investigating traditional plants as antifertility herbal medicine for men. Studies on antifertility effects of unripe papaya seeds have been done. However, similar studies on hexane fraction extract have not yet been done. In this study, unripe seeds were collected from local Balinese papaya (Carica papaya) fruits. Objective: This study was aimed to assess the effect of unripe papaya seeds hexane fraction extract on spermatogenesis and the testosterone level of male mice. Hexane fraction extract of unripe papaya seeds contains glycosides and triterpenoids, which is assumed to have an antifertility property, so it can be used as a male contraceptive, although the mechanism of action remains to be elucidated. Method: This study used pre-test and post-test control group design, using 30 male mice of balb C strain, 12 weeks of age, weighing 20-22 gram, which were randomly grouped into 3 groups, each consisting of 10 male mice. One control group (P0 = control group) was given double-distilled water, and two treatment groups were given hexane fraction extract of unripe Carica papaya seeds 20 mg/20gram/day, and methanolic extract of unripe Carica papaya seeds 20 mg/20 gram/day (P1 and P2, respectively). After 36 days of treatment, evaluation of the testes and blood of the male mice was conducted. Results: Data were analysed by normality test of Kolmogorov-Smirnov Goodness of Fit, homogeneity test, and Anova test. This study showed that spermatogonia A, primary pachytene spermatocytes, spermatid and Sertoli cells were decreased significantly (p < 0,05) but Leydig cells and testosterone levels were not decreased significantly (p > 0,05). Conclusion: It can be concluded that hexane fraction extract of unripe Carica papaya seeds can decrease the mean number of spermatogonia A cells, spermatocyte of primary pachytene spermatocytes, spermatid and Sertoli cells better than methanolic extract of unripe Carica papaya seeds.